HIV-Associated Cryptococcal Meningitis Occurring at Relatively Higher CD4 Counts. (16th October 2018) - Tugume, Lillian; Rhein, Joshua; Hullsiek, Kathy Huppler; Mpoza, Edward; Kiggundu, Reuben; Ssebambulidde, Kenneth; Schutz, Charlotte; Taseera, Kabanda; Williams, Darlisha A; Abassi, Mahsa; Muzoora, Conrad; Musubire, Abdu K; et al.
Abstract : HIV-infected individuals with CD4 count >100 cells/μL with cryptococcal meningitis presented more frequently with altered mental status despite having a 10-fold lower fungal burden. The survival by extremes of low and high CD4 are consistent with the damage-response framework theory. Abstract: Background: Cryptococcal meningitis can occur in persons with less-apparent immunosuppression. We evaluated clinical characteristics and outcomes of persons with HIV-related Cryptococcus presenting with higher CD4 counts. Methods: We enrolled 736 participants from 2 prospective cohorts in Uganda and South Africa from November 2010 to May 2017. We compared participants with CD4 <50, 50–99, or ≥100 cells/μL by clinical characteristics, cerebrospinal fluid (CSF) parameters, and 18-week survival. Results: Among first episode of cryptococcosis, 9% presented with CD4 ≥100 cells/μL. Participants with CD4 ≥100 cells/μL presented more often with altered mental status (52% vs 39%; P = .03) despite a 10-fold lower initial median CSF fungal burden of 7850 (interquartile range [IQR] 860–65500) versus 79000 (IQR 7400–380000) colony forming units/mL ( P < .001). Participants with CD4 ≥100 cells/μL had higher median CSF levels of interferon-gamma, interleukin (IL)-6, IL-8, and IL-13, and lower monocyte chemokine, CCL2 ( P < .01 for each). Death within 18 weeks occurred in 47% with CD4 <50, 35% with CD4 50–99, and 40% with CD4 ≥100 cells/μL ( P = .04). Conclusion: HIV-infected individuals developing cryptococcal meningitis with CD4 ≥100 cells/μL presented more frequently with altered mental status despite having 10-fold lower fungal burden and with greater Th2 (IL-13) immune response. Higher CD4 count was protective despite an increased propensity for immune-mediated damage, consistent with damage-response framework. Clinical trial registration: NCT01075152 and NCT01802385.